2017
DOI: 10.1021/acs.biochem.7b00281
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Dynamics in the BamA β-Barrel Seam

Abstract: BamA is an essential component of the β-barrel assembly machine (BAM) responsible for insertion and folding of β-barrel Outer Membrane Proteins (OMPs) in Gram negative bacteria. BamA is an OMP itself, and its β-barrel transmembrane domain is thought to catalyze OMP insertion and folding, although the molecular mechanism remains poorly understood. Crystal structures of BamA and complementary molecular dynamics simulations have shown that its β-barrel seam (the interface between the first and last barrel strands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 43 publications
9
65
0
Order By: Relevance
“…There, it was found through disulfide cross-linking that β-barrel precursors translocate into the Sam50 channel and then enter the lateral gate as β-hairpins, interacting with both N-and C-terminal strands of Sam50 (51). Nonetheless, in another recent study, it was found that a disulfide-locked lateral gate still accelerates the insertion of an eight-strand β-barrel OmpX, which runs contrary to the hybrid barrel model (34). Regardless of the exact mechanism, membrane thinning, as consistently observed in our simulations, plays a vital role in OMP insertion by significantly lowering the insertion free-energy barrier.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There, it was found through disulfide cross-linking that β-barrel precursors translocate into the Sam50 channel and then enter the lateral gate as β-hairpins, interacting with both N-and C-terminal strands of Sam50 (51). Nonetheless, in another recent study, it was found that a disulfide-locked lateral gate still accelerates the insertion of an eight-strand β-barrel OmpX, which runs contrary to the hybrid barrel model (34). Regardless of the exact mechanism, membrane thinning, as consistently observed in our simulations, plays a vital role in OMP insertion by significantly lowering the insertion free-energy barrier.…”
Section: Discussionmentioning
confidence: 98%
“…The BamA β1 − β16 seam has become the centerpiece for several models for OMP assembly including the so-called "hybrid barrel model" (32,33) and the "passive model" (34). In the passive model, the principal role played by the seam is to prime the membrane for OMP insertion.…”
mentioning
confidence: 99%
“…Consistent with this model, engineered disulfide bonds that prevent the opening of the putative lateral gate are lethal in E. coli (17). Disulfide locking of the BamA b-barrel, however, does not effectively block OMP assembly in vitro (16,18,19). Molecular dynamics simulations (20, 21) and other studies (22) that suggest that the BamA β-barrel causes thinning of the adjacent membrane have led to an alternative model in which the Bam complex catalyzes OMP assembly by creating a local deformation of the lipid bilayer.…”
mentioning
confidence: 81%
“…In an alternative model, it has been proposed that the Bam complex facilitates the membrane integration of folded or partially folded β barrels by perturbing the lipid bilayer (Noinaj et al ., 2013 ). This model is supported by evidence that at least some OMPs begin to fold prior to membrane integration (Ieva et al ., 2008 ;Lee et al ., 2016 ;Sikdar et al ., 2017 ), that BamA lowers the kinetic barrier for OMP insertion imposed by lipid head groups (Gessmann et al ., 2014 ), that BamA exerts a greater catalytic effect on OMP folding in thicker bilayers (Schiffrin et al ., 2017 ), and that BamA is highly dynamic in liposomes (Doerner and Sousa, 2017 ). The crystal structure of the Bam complex shows that the POTRA domains and the four lipoproteins form a ring below the BamA β barrel.…”
Section: Introductionmentioning
confidence: 99%